2022
DOI: 10.3390/educsci12100694
|View full text |Cite
|
Sign up to set email alerts
|

Infusing Mindset through Mathematical Problem Solving and Collaboration: Studying the Impact of a Short College Intervention

Abstract: After experiencing years of procedural teaching in K-12 mathematics classrooms, many students arrive at college with ideas about, and approaches towards, mathematics that are not helpful to their learning. Students’ prior experiences and misconceptions can then negatively impact their experiences in university STEM courses. This paper describes a short course in the “big ideas” of calculus, that offered students an approach of problem-based learning, combined with mindset messages, otherwise known as a “mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…An 293 influenced problem-solving skills indirectly. The moderating factor of this influence is -solving mathematical problems [11]. Therefore, learners must develop the mindset needed for 21st-century skills [12].…”
Section: Introductionmentioning
confidence: 99%
“…An 293 influenced problem-solving skills indirectly. The moderating factor of this influence is -solving mathematical problems [11]. Therefore, learners must develop the mindset needed for 21st-century skills [12].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, it has been found that a mathematical mindset is related to motivational factors, self-confidence, perception, students' knowledge, and interest, as well as teacher support (Aguilar, 2021;Boyer & Mailloux, 2015;Hannula et al, 2004;Heinze et al, 2005;Tambunan, 2018). Research on the effectiveness of mindset interventions, which instill the idea that intelligence can be developed and that effort is an essential part of learning, has been conducted across different age groups and subjects, highlighting its importance (Blackwell et al, 2007;Boaler et al, 2022;Dweck, 2006). When students change their mindset and believe they can learn at higher levels, they alter their learning trajectory (Boaler et al, 2022).…”
mentioning
confidence: 99%
“…Self-perception related to mathematics is the first barrier that students encounter in learning mathematics and contributes to negative attitudes. This is because students recognize their lack of foundational knowledge in mathematics as a result of their initial perception of the difficulty of mathematical reasoning (Aguilar, 2021;Aswin & Herman, 2022;Boaler et al, 2022;Nurita et al, 2022). Self-efficacy is part of the mindset (Rhew et al, 2018), meaning that students with a growth mindset are more likely to learn mathematical knowledge, actively engage in the learning process, and creatively connect mathematical ideas.…”
mentioning
confidence: 99%
See 2 more Smart Citations